The Knowledge Nexus in Teacher Qualification: Education Research and Norwegian General Teacher Education 1970-2020—Institutional and Intellectual Interchanges - Jarning, Harald (Nordic Journal of Comparative and International Education, 2020)
Research in teacher education institutions has undergone a rapid dual process of expansion and differentiation over the past decades. A major effort in this article is to register and discuss key institutional and intellectual changes in education research linked to the case of Norway. This overview gives a background for discussion of the impacts from the growing research in teacher education units regarding the knowledge dynamics in general teacher education. In the wake of the less segmented research policies of the last quarter of a century, emphasis on direct contributions of research to the qualification of teachers has become a highly visible issue. I will argue that with the concurrent expansion and diversification of education research, it has become vital to understand how the internal hybrid knowledge dynamics can support the quest for greater coherence in the qualification and professional repertoire of new teachers. Simultaneously, awareness of how research-driven knowledge specialisation can increase academic drift, fragmentation and professional disorientation in teacher education programmes is needed. In the mapping of research trajectories in the field of general teacher education, the contrasts between epistemic patterns in the didactic phase of secondary disciplinarisation are compared to the educational phase. Awareness across teacher education faculty of such research-driven changes can support receptivity towards disciplinary as well as cross-disciplinary challenges and of scholarly care for a more thorough and balanced professional knowledge base. Such common professional orientations can also support the cultivation of interchanges between research, teaching and innovation, and within and across arenas and disciplines contributing to the qualification of good teachers.